Music Therapy in the Treatment: of People with Hearing Deficits: A Review of Selected Strategies - Surma Joanna (Musicology Today)
The paper deals with the question of music making in people with hearing deficits, showing the main advantages of such practice. It examines differences between ‘hearing’ in a medical sense and ‘musical hearing’ which is semantically much wider and involves different parts of the brain. Using various examples, the paper proves the possibility of music making even in the case of acute, bilateral or prelingual hearing impairment, but emphasises the necessity of Individualized Education Programme implementation to successfully face challenges posed by hearing deficits. The paper describes the main difficulties and challenges that deaf individuals face during the music learning process, and sums up strategies for musical pedagogy recommended in research studies since the second half of the twentieth century. Elements such as melodic patterns, rhythm and harmony are discussed. The teaching methodology presented in this paper focuses on multisensory approaches that may compensate for hearing loss, underlining such aspects as imagination, movement coordination, visual and haptic stimuli. Different types of hearing loss are presented, depending on their medical causes, hypoacusis level, onset time, and articulation ability in the context of music making. The article emphasises the beneficial role of active music-making for the patient’s well-being, especially for memory training, developing the emotional sphere, improvement of prosodic elements in speech, and tinnitus relief.